Applying Quantitative Approaches in the Use of RWE in Clinical Development and Life-Cycle Management. (2nd January 2023) - He, Weili; Fang, Yixin; Wang, Hongwei; Chan, Ivan
Abstract: Randomized controlled clinical trials (RCTs) have been the gold standard for the evaluation of efficacy and safety of medical interventions. However, the costs, duration, practicality, and limited generalizability have incentivized many to look for alternatives. In recent years, we have seen an increasing usage of real-world data (RWD) and real-world evidence (RWE) in clinical development and life-cycle management, although many challenges remain. While there are numerous publications in RWD and RWE areas, strategic planning and tactical execution perspectives from an end-to-end process are still lacking, including the use of RWEs not only in regulatory settings but also in nonregulatory settings along with organizational infrastructure considerations. We attempt, to the extent possible, to fill this void by providing thoughts on addressing the key challenges and use cases we have seen in real-world (RW) settings. As quantitative scientists working in drug development, we see tremendous potentials in applying quantitative approaches in the use of RWE. To that end, we include discussions on opportunities where statisticians could play a key role in RWE research both in and beyond regulatory settings.